Analysis of Types of Sentences Based on Forms and Meanings in the Short Story Rembulan in the Eyes of Mother by Asma Nadia - Nurul Jumrah; Asih Kusumawati; Khanifa Kinanthi Aulina; Asep Purwo Yudi Utomo (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2023)
A literary work does not only consist of one sentence, but there are many types of sentences that can be analyzed. Therefore, the researcher is interested in bringing up a literary work in the form of the short story